Dynamic regulation of molecular chaperone gene expression in polyglutamine disease. - Huen, N.Y.; Chan, H.Y. (Biochemical and Biophysical Research Communications, 2005)
Expanded polyglutamine disease proteins cause adult-onset progressive neurodegeneration. Constitutive overexpression of the Hsp70 molecular chaperone is capable of suppressing polyglutamine neurodegeneration. We showed that endogenous Hsp70 expression was induced, at both transcriptional and translational levels, in Drosophila models of polyglutamine disease. Soon after the endogenous Hsp70 induction reached a maximum level at larval stage, its expression declined progressively with age. We further showed that cellular heat shock response remained intact in aged flies, indicating the decline of Hsp70 levels observed in polyglutamine-expressing flies is not due to normal ageing. In contrast to the well-documented polyglutamine suppression caused by constitutive Hsp70 overexpression, no suppression of degeneration was observed when inducible copies of hsp70 transgenes were instead coexpressed. This supports a transcriptional dysregulation of endogenous hsp70 gene induction in polyglutamine flies. Altogether, we propose that transcriptional malfunctioning of molecular chaperone gene expression contributes to the late-onset and progressive nature of polyglutamine toxicity.